2014
DOI: 10.1097/igc.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Incidence in Ontario Women: Differing Sociodemographic Gradients by Morphologic Type (Adenocarcinoma Versus Squamous Cell)

Abstract: This study identified significantly higher incidence of cervical cancer in low-income neighborhoods in Ontario. The association was especially pronounced for squamous cell carcinoma and varied by time period for adenocarcinoma. Improvements to screening and prevention efforts against oncogenic human papillomavirus strains would increase the detection of cervical cancer, adenocarcinoma especially, and may further reduce cervical cancer incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
1
0
2
Order By: Relevance
“…Meanwhile, in Uganda, less education was associated with a higher risk of contracting high-risk human papillomavirus (HR-HPV) ( 66 ). In Canada, there were more CC cases in rural and poorer areas than in urban or affluent locations ( 67 ). A meta-analysis suggested that low SES (OR: 2.68) or a low level of education (OR: 1.97) increases the risk of developing CC ( 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, in Uganda, less education was associated with a higher risk of contracting high-risk human papillomavirus (HR-HPV) ( 66 ). In Canada, there were more CC cases in rural and poorer areas than in urban or affluent locations ( 67 ). A meta-analysis suggested that low SES (OR: 2.68) or a low level of education (OR: 1.97) increases the risk of developing CC ( 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…За даними різних авторів [2,3,4,10], аденокарцинома шийки матки (АКШМ) становить 8-26 % випадків усіх РШМ, але має більш несприятливий прогноз ніж плоскоклітинний РШМ. Крім того, АКШМ рідше виявляють на ранніх стадіях, оскільки пухлина локалізується в цервікальному каналі і не візуалізується при гінекологічному огляді [3,4,5,8,10].…”
unclassified
“…Проте, незважаючи на актуальність проблеми АКШМ, у вітчизняній та зарубіжній літературі цій нозології, на відміну від плоскоклітинного РШМ, приділяється незаслужено мало уваги [4,8,10]. Ці роботи поодинокі та присвячені, в основному, методам лікування занедбаних її форм.…”
unclassified